Facilitators of and Barriers to Gastric Cancer Screening Among Korean Americans. Issue 4 (July 2017) - Sin, Mo-Kyung; Kim, Il-Ho
Abstract : Background: Gastric cancer is the most highly prevalent cancer among Korean Americans, occurring at a higher rate than among other Asian Americans and non-Latino Whites. However, little is known about the culturally specific barriers to gastric cancer screening among Korean Americans. Objective: The aim of this study was to explore facilitators of and barriers to gastric cancer screening among Korean Americans. Methods: In this qualitative focus group study, a convenience sample of 50 Korean Americans aged 21 to 75 years was recruited from the Puget Sound area of Washington with the assistance of Korean churches. Five focus groups of 6 to 8 and 1 focus group of 13 were conducted in a church, a café, and an apartment community center. The focus group discussions lasted approximately 30 minutes to 1 hour. Directed content analysis was used to analyze the data. Results: Facilitators included exposure to Korean media, history and prevalence of gastric problems, perceptions concerning positive aspects of the healthcare system in South Korea, physician recommendations, technology, and church health fair. Barriers included a lack of knowledge, finance/lack of health insurance, fear of test results, perceptions of an inconvenient American healthcare system, a lack of knowledge of American healthcare providers on culturally related health risks, a dislike of medical procedures, and no preventive measures. Conclusions: Sociocultural facilitators and barriers add new knowledge in a field with scarce information available. Implications for Practice: The study findings lay the groundwork for developing culturally relevant interventions that enhance healthcare providers' awareness while empowering Korean Americans to prevent gastric cancer.